To solve the equation \( \frac{11}{s+3} + 4 = 5 \), we can follow these steps:
- Subtract 4 from both sides:
\[ \frac{11}{s+3} = 5 - 4 \]
This simplifies to:
\[ \frac{11}{s+3} = 1 \]
- Now, we can eliminate the fraction by multiplying both sides by \( s + 3 \):
\[ 11 = 1 \cdot (s + 3) \]
This simplifies to:
\[ 11 = s + 3 \]
- Next, isolate \( s \) by subtracting 3 from both sides:
\[ s = 11 - 3 \]
This gives us:
\[ s = 8 \]
So, the solution is \( s = 8 \).
You can check your work by plugging \( s = 8 \) back into the original equation:
\[ \frac{11}{8 + 3} + 4 = 5 \] \[ \frac{11}{11} + 4 = 5 \] \[ 1 + 4 = 5 \]
Since both sides are equal, the solution \( s = 8 \) is correct.